Avaliação formativa de estudantes de enfermagem em estágio curricular supervisionado - Ramos, Tierle Kosloski (2024)
The Supervised Curricular Internship provides nursing students with the opportunity to experience everyday situations in the work of nurses, through the acquisition and improvement of skills and competencies that underpin professional practice. In this training context, with regard to learning assessment, it is recommended to use strategies that enable diagnostic, formative and summative assessment. General objective: To develop an instrument for the formative assessment of nursing students in supervised curricular internships. Specific objectives: to develop an Instrument for Formative Assessment of Nursing Students in Supervised Curricular Internships; to validate the content of the instrument with a panel of experts; to evaluate the usability and reliability of the Instrument for Formative Assessment of Nursing Students in Supervised Curricular Internships with the target audience. Method: a methodological, quasi-experimental before-and-after study, carried out in three stages: preparation, validation and evaluation of the instrument, supported by Philippe Perrenoud's theoretical framework of formative assessment. The instrument was developed in January 2023, based on an integrative literature review and official documents from the Ministry of Education and Culture, the Federal Nursing Council and the Brazilian Nursing Association. Validation took place between June and September 2023, using the modified e-Delphi technique. The data was collected online using the Google forms® tool, with the instrument presented in the form of a four-point Likert scale, in which 12 psychometric criteria were assessed. In the first round, 24 experts took part, while in the second round, 12 experts were located through searches on the curriculum lattes platform, institutional websites and snowball sampling. To evaluate the instrument, a quasi-experimental before-and-after study was carried out between October and December 2023 with the target audience (students, supervising nurses and teachers), using the Instrument for Formative Evaluation of Nursing Students in Supervised Curricular Internships. The data was stored in spreadsheets and then analyzed using the Statistical Package for Social Sciences (SPSS)® version 28.0. The reliability and internal consistency of the instrument was analyzed using the Cronbach's alpha coefficient, and the overall validation of the psychometric criteria, as well as the blocks and items of the instrument, was assessed using the Content Validity Index, with CVI ≥ 0.80 being considered adequate. The variables were described by mean and standard deviation and compared between the groups using one-way ANOVA. For the comparison between the domains, ANOVA for repeated measures together with the Bonferroni test was applied. The test and retest results were evaluated using both the Student's t-test for paired samples and the Intraclass Correlation Coefficient. Results: In the first round, 24 experts participated, evaluating the instrument with a CVI of 0.89. In the second round, 12 experts took part, obtaining a final validity index of 0.92 and a reliability of 0.993. In the evaluation with the target audience, there was agreement between the groups on the mean scores of the domains. The instrument proved to be reliable with a Cronbach's alpha of 0.95. In some items, there was low agreement and a significant difference, with no possibility of reproducibility. The domains showed agreement and reproducibility. No sensitivity to change was identified. Conclusion: The instrument was validated by a panel of experts representing all regions of the country, obtaining an adequate evaluation of the items and domains, as well as the other guiding elements, demonstrating that the instrument is valid and reliable. The instrument has the reliability and reproducibility to be implemented in the formative evaluation of internship learning.